Pelatihan Penerapan Aspek Teknologi Pengawetan Hijauan Pakan Ternak Di SMK Negeri 1 Purbolinggo - Reni Asih, Diah; Anwar, Rohmatul; Puspitaningrum, Citra; Subakti Prastiyo, Subakti Prastiyo (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Ammonia straw is a forage preservation process using ammonia. Giving ammonia to straw has several advantages including increasing straw nitrogen, increasing palatability, consumption and digestibility of feed. The purpose of this service activity is to conduct training on the application of technological aspects of preserving forage fodder at SMK Negeri 1 Purbolinggo. The method used is giving theories to students and continued by practicing directly in making ammoniation.. Based on the observations, it was seen that the students were quite enthusiastic during the training activities for making ammoniated rice straw. The manufacture of ammonia using rice straw as the basic material was successfully carried out which was marked by the criteria for color, smell, texture, and fungal conditions from the ammoniated rice straw which was produced under normal conditions so that it was suitable for consumption by cattle. Ammonia rice straw can be used as a source of animal feed and one of the concepts of an integrated agricultural agribusiness business between animal husbandry and agriculture.